Evaluating milk quality indicators in the era of antimicrobial stewardship: A study of tennessee dairy farms (2011–2023) - Roderick T. Salvador; Jessica Vidlund; Chika C. Okafor (PLoS ONE, 2025)
This study evaluated temporal and seasonal trends in milk quality parameters: somatic cell count (SCC), fat, and protein content among Tennessee dairy farms from 2011 to 2023, with reference to the 2017 implementation of the Veterinary Feed Directive (VFD). A total of 8,357 herd-month records from the Tennessee Dairy Herd Improvement Association (DHIA) were analyzed using linear mixed-effects models to assess year, season, and policy-period effects while accounting for clustering by herd size. Results showed a significant decline in SCC (−17.5%, p < 0.001) and significant increases in milk fat (+8.48%) and protein (+2.95%) over the study period. Seasonal variation was pronounced, with higher SCC and lower components during summer months. Although improvements in milk quality coincided with the post-VFD period, the directive primarily targeted antimicrobials in feed and water rather than intramammary therapy; thus, observed changes likely reflect continued advances in herd management, nutrition, and genetics rather than a direct regulatory effect. These findings highlight the role of environmental and management adaptation in sustaining milk quality under evolving production and policy contexts.